Avaliação da eficiência da pré-inoculação com Bradyrhizobium spp. em sementes de soja tratadas industrialmente - Anghinoni, Fernanda Brunetta Godinho (2016)
Nitrogen (N) is an essential nutrient, greatly demanded by the soybean crop. Currently, the main way for the plant to supply N demand is through biological nitrogen fixation, which in addition to the replacement of the nitrogen chemical fertilization, also has the capacity to supply all the nutrient demand required for the soybean crop. The pre-inoculation consists in the inoculation of nitrogen fixing bacteria on the seeds prior to sowing, which is a practice that has been used in many other countries. However, the use of this technique depends especially on bacteria's ability to survive while inoculated, on the type of treatment used in seeds processing and on its storage conditions. Thus, this study aims to evaluate the effect of pre-inoculation compared to the standard inoculation in soybean seeds industrially treated, for two consecutive years, on the plants nodulation, on N content and on crop yield components. The experiment was conducted in the agricultural years of 2013/14 and 2014/15 in the Fazenda Experimental de Iguatemi (FEI), of the Universidade Estadual de Maringá (UEM). The experimental design consisted in a randomized block, with 10 treatments and four replications. Different combinations of insecticides and fungicides for industrial seed treatment, standard seed inoculation, inoculation with LT inoculant at different periods of pre-inoculation (0, 5 and 10 days), as well as a treatment with nitrogen fertilization and an absolute control treatment. At field and laboratory the following determinations were carried out: number and mass of nodules at flowering, dry matter of shoots and roots, nitrogen content in shoots and grains, number of pods per plant and mass of a thousand seeds. The results showed that the use of LT inoculant along with the carbendazim and thiram in addition to imidacloprid and thiodicarb provide plants with greater dry mass of shoots. Results showed that seeds can be inoculated with LT inoculant and stored for up to 10 days, without decreasing the yield components of soybean. The use of conventional nitrogen fertilization is not recommended as it may compromise the weight of a thousand seeds and the nitrogen content in the seeds, without affecting crop productivity.